2021
DOI: 10.3389/pore.2021.1610013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evaluation of Endometrial Dedifferentiated Carcinoma, Endometrioid Carcinoma, Carcinosarcoma, and Serous Carcinoma Using a Custom-Made Small Cancer Panel

Abstract: It is often difficult to histologically differentiate among endometrial dedifferentiated carcinoma (DC), endometrioid carcinoma (EC), serous carcinoma (SC), and carcinosarcoma (CS) due to the presence of solid components. In this study, we aimed to categorize these carcinomas according to The Cancer Genome Atlas (TCGA) classification using a small custom-made cancer genome panel (56 genes and 17 microsatellite regions) for integrated molecular diagnosis. A total of 36 endometrial cancer cases with solid compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…12,27 Moreover, the present case is TMB-high (endometrial lesion) or TMB-ultrahigh (pelvic lesion) and MSI-low in both elements, which is not consistent with MMR-deficient subtype. 32 Actually, the every tumor element in the present case was positive for MMR proteins, and therefore, the POLE p.T457del mutation is suggested to be attributable to ultramutator phenotype.…”
Section: Discussionmentioning
confidence: 58%
“…12,27 Moreover, the present case is TMB-high (endometrial lesion) or TMB-ultrahigh (pelvic lesion) and MSI-low in both elements, which is not consistent with MMR-deficient subtype. 32 Actually, the every tumor element in the present case was positive for MMR proteins, and therefore, the POLE p.T457del mutation is suggested to be attributable to ultramutator phenotype.…”
Section: Discussionmentioning
confidence: 58%
“…POLE mutated endometrial carcinosarcoma showed an excellent prognosis similar to that of POLE mutated endometrioid endometrial cancers, supporting their inclusion in the same low-risk category for treatment purposes in the current European Society of Gynecological Oncology (ESGO), the European SocieTy for Radiotherapy and Oncology (ESTRO), and the European Society of Pathology (ESP) guidelines 9. On the other hand, the prognosis of p53-abn and non-specific molecular profile endometrial carcinosarcoma was even worse than that of their endometrioid/serous counterparts, while that of MSI-H/dMMR tumors was unclear and remains to be clarified 4 20–27 Table 1. shows the current evidence regarding the molecular/genomic profiling of endometrial carcinosarcomas.…”
Section: Molecular Landscapementioning
confidence: 71%
“…Future trials should focus on the efficacy of pattern-specific treatments, selected based on the specific signatures of endometrial carcinosarcoma. Several molecular studies described mutations or alterations of multiple genes and pathways in endometrial carcinosarcoma, including c-KIT, TKR, VEGF, EGFR, Her2/neu, NTRK, PI3K/AKT/mTOR pathway , WEE1, KRAS, EXP, BRCA1/2 , and other genes related to cell-cycle regulation (including homologous recombination deficiency), histone modification, and chromatin remodeling, which may all represent potential targets 21–27…”
Section: Novel Therapeutic Agents and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations